2021
DOI: 10.1038/s43247-021-00156-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of scientists held by US students can be broadened through inclusive classroom interventions

Abstract: More diverse representation in undergraduate classrooms may be an important step towards turning science, technology, engineering, and mathematics (STEM) disciplines into more inclusive communities. In the United States of America, the individuals whose work is discussed in typical introductory science courses collectively do not represent the diversity of students’ identities in the classroom and further reinforce existing stereotypes of scientists as male, white, and aged. Here we report on the implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…A 2021 study of STEM students in the United States 10 showed that the classical scientists who developed unifying theories, as presented in the classroom, did not represent the diversity of student identities. In fact, the scientists were predominantly white European males.…”
Section: Perception Of Sciencementioning
confidence: 99%
“…A 2021 study of STEM students in the United States 10 showed that the classical scientists who developed unifying theories, as presented in the classroom, did not represent the diversity of student identities. In fact, the scientists were predominantly white European males.…”
Section: Perception Of Sciencementioning
confidence: 99%
“…Developing this knowledge requires an understanding of a variety of terms commonly used in the history of racism in the United States. Sources have been provided in the context to help faculty become familiar with this terminology ( 44 – 47 ).…”
Section: Dei Rubric Criteriamentioning
confidence: 99%
“…Prioritize inclusive teaching practices in conservation courses by embracing the tenets of inclusive course design, active learning modalities and service learning techniques, to encourage broader participation and interest in conservation sciences. Recommended reading [64][65][66][67].…”
Section: Racism In Conservation Science and Practice Todaymentioning
confidence: 99%